EFFECT OF OMEGA-3 AND 6 POLYUNSATURATED FATTY ACIDS ON DIABETES MELLITUS TYPE 2.: http://doi.org/10.46536/jpumhs/2023/13.03.448 - Imtiaz Ahmad Jaat1 , Yasmin Shaikh2 , Ahsan Alam3 , Ghulam Mujadid4 , Nida5 , Farzah Farooqui6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
OBJECTIVES: To evaluate the effects of optimized proportions of Omega-3 and Omega-6 polyunsaturated fatty acids on diabetes mellitus type 2.METHODOLOGY: The experimental analytical study was carried out in the research lab of Isra University Hospital Hyderabad from March to August 2022. A total 50 male healthy albino Wistar rats weighing about 200  250 grams were procured from the animal house of Sindh Agricultural University Tandojam. After completion of the acclimatization period, rats were initially divided into group A and B Control n=10 and Experimental groups n=40 respectively. The control group received a standard chow diet and water ad libitum for one month. The experimental group rats were injected with Alloxan 150mg/kg body weight mixed with 2ml normal saline intra-peritoneally to induce diabetes in the experimental groups. After induction experimental rats were further divided into 4 groups n=10. Group B1 Diabetic control group after inducing diabetes fed with a normal chow diet ad labitum for 30 days. Group B2 Experimental Omega-3 Treated Group was fed a diet mixed with 0.3gms/kg b.w of Omega-3 fatty acid for 30 days.Group B3 Experimental Omega-6 Treated Group fed diet mixed with 0.3gms/kg b.w of Omega-6 fatty acid for 30 days. Group B4 Experimental Combination Treated Groups was fed a diet mixed with equal amounts of Omega-3 and Omega-6 fatty acids in a dose of 0.3gms/kg b.w for 30 days.RESULT: A significant difference between the mean body weight of rats of groups A, B1, B2, B3, B4 p<0.05. The mean level of FBS before and Mean level of FBS after induction showed statistically significant at p-values <0.05 and <0.001 respectively. The mean level of C-reactive proteinmg/L in Control was 0.11±0.03 while in group B1 rats was 0.61±0.12 in B2 rats was 0.24±0.04, in B3 rats was 0.31±0.08 and in B4 rats was 0.17±0.03. The C reactive levels were found to be significantly elevated in group B1 compared with A, B2, B3, and B4 rats. CONCLUSION: It is concluded from the present study that the administration of equal proportions of Omega-3 and Omega-6 polyunsaturated fatty acids plays a significant role in regulating body homeostasis and also impacts glycemic control by improving markers of insulin resistance